Industry evolution, submarket dynamics and strategic behaviour among firms in offshore wind energy. (April 2017) - Houman Andersen, Poul; Drejer, Ina; Gjerding, Allan Næs
This paper contributes to the understanding of competition and industry evolution by analysing how submarket dynamics and agency influence the development of the emerging industrial field of Danish offshore wind energy. We argue that industry evolution is sensitive to the balance between integration, overlap and disintegration across submarkets. This balance depends on how strategic intent and behaviour influence submarket dynamics, leading to the conclusion that effects of agency and managerial intent should play a more prominent role in studies of industry evolution.